The Inclusion of the Social Factor in Polish Criminal Proceedings - Starybrat, Julia (Central European Academy Law Review, 2025)
This study analyses the inclusion of the social factor in Polish criminal proceedings, focusing on its significance for the principle of publicity and social over- sight of the judiciary. It discusses case law concerning the openness of proceedings, highlighting its impact on procedural practice and the interpretation of legal provisions. Moreover, it presents the role of social organisations and social representatives in criminal proceedings, emphasising their competencies and importance in protecting the public interest. Further, it focuses on the institution of lay judges, examining their influence on the functioning of the judiciary and the challenges related to their participation in adjudication. It is emphasised that the social factor enhances the transparency of proceedings and public trust in the justice system. However, its effectiveness depends on appropriate mechanisms ensuring its efficiency and impartiality.